Improved Performance of Water Supply System Sawah Liek and Tungku Sadah PDAM Kota Padang Panjang - Ridwan Ridwan (Jurnal Serambi Engineering, 2021)
Sawah Liek and Tungku Sadah have increased turbidity  during the rainy season, 629 NTU. Sawah Liek and Tungku Sadah are 845 m and 888 m above sea level and flow by gravity at  Sungai Andok Reservoir, 802 m. Sawah Liek has a  production of  5 l/s for  428 customers and Tungku Sadah 10 l/s for  2,806 customers. One of the causes of turbidity fluctuation during rain is planting  activities which degrade the area of land cover, increase runoff and minimize infiltration into the area  that the flow from the source decreases  every year.  Water consumption for customers of Sawah Liek is 202 l/person/day and Tungku Sadah 62 l/person/day is smaller than the category of small  towns of 130 l/person/day. The installed slow sand filter is unable to handle the turbidity during the rain in  exceeds of 50 NTU. The maximum produced  by the installed slow sand filter is 2.67 l/s. Changes in the function of the filter installed at a high-speed sand filter can increase production to 26.7 l/s and overcome turbidity fluctuations can be accomplished  by improving the system with a complete treatment facility  or an incomplete processing facility  consisting of a screen, a large  chamber, coagulation, and flocculation, filtration and disinfection.